Dimensions of Cultural Responsiveness in the Assessment Practices of Bilingual Teachers - Pournik, Shahram; Shojaei, Maedeh; Kariminia, Saeed (Assessment and Practice in Educational Sciences, 2023)
This study aimed to explore the dimensions of cultural responsiveness in the assessment practices of bilingual teachers working in diverse educational settings in Tehran. The study employed a qualitative research design to gain in-depth insights into how bilingual teachers conceptualize and implement culturally responsive assessment. Data were collected through semi-structured interviews with 26 bilingual teachers selected via purposive sampling. All participants had at least three years of teaching experience in bilingual classrooms. Interviews were conducted in Persian, transcribed verbatim, and analyzed using thematic analysis with the support of NVivo software. The data collection continued until theoretical saturation was reached. Three overarching themes emerged from the data: (1) culturally sensitive assessment design, (2) reflective and responsive teaching practice, and (3) institutional and structural considerations. Participants described strategies such as adapting assessment content and rubrics to reflect cultural backgrounds, using multimodal assessment formats, and avoiding culturally biased language. Teachers also engaged in reflective practices, emphasized student voice, and adapted feedback to align with students’ cultural contexts. However, they also reported significant systemic constraints, including standardized testing mandates, limited professional development, and lack of institutional support. Despite these challenges, bilingual teachers demonstrated agency and creativity in implementing assessment practices that honored students’ cultural and linguistic diversity. The findings highlight the complex, multidimensional nature of culturally responsive assessment and the critical role of bilingual teachers in navigating and transforming conventional assessment practices. Addressing structural barriers and providing targeted professional development are essential steps toward equitable assessment in multilingual educational contexts.